Robotic approach to the reduction of dental anxiety in children. (17th August 2020) - Kasimoglu, Yelda; Kocaaydin, Simin; Karsli, Emine; Esen, Merve; Bektas, Irmak; Ince, Gökhan; Tuna, Elif Bahar
Abstract: Objective: We introduced a humanoid robot for the use of techno-psychological distraction techniques in children aged 4–10 to reduce their anxiety and improve their behaviour during dental treatment. Materials and methods: Two hundred children (98 boys, 102 girls; mean age: 6.5 ± 1.66 years) appointed for first time for dental caries were included and randomly divided into two groups [ N  = 100 for each group; RG: Robot Group (accompanied by the robot), CG: Control Group (without robot accompaniment)]. Half of the children were treated under local anaesthesia (infiltration anaesthesia) ( n  = 50 within each group) and half of the children were treated without any local anaesthesia ( n  = 50 within each group) within each group. The success rate of the new robotic distraction technique was evaluated by using Parental Corah Dental Anxiety Scale, Facial Image Scale (FIS), physiological pulse rate and Frankl Behaviour Rating Scale (FBRS). Result: Pulse rates, which measured during treatment and after treatment, were statistically higher in CG than in RG ( p  < .05). After dental treatment, the FIS score was significantly higher in CG than RG ( p  < .05). 88.3% of the children in RG stated that they wanted the robot to be with them at the next treatment session. Conclusions: Robotic technology can successfully help in coping with dental anxiety and stress, and helps children to behave better in dental office.